Insecticides may compromise the benefits of tree-crop diversification on arthropod biodiversity in cocoa agroforestry smallholdings - Zakaria, Najihah; Norhisham, Ahmad R.; Yasmin, Ilya; Yahya, Muhammad Syafiq; Sanusi, Ruzana; Azhar, Badrul (Informa UK Limited, 2024)
Arthropods play vital roles in ecosystem functions, yet their distribution is subjected to environmental factors. Hence, this study investigates the impact of habitat features on arthropod communities within cocoa smallholdings under different farming practices: agroforestry and monoculture systems. We conducted arthropod sampling using yellow sticky traps and assessed the habitat features at each plantation twice to capture temporal variations in arthropod populations. The study recorded 2945 individual arthropods belonging to eight different functional groups. The most abundant functional group was saprophagous, followed by phytophagous, parasitoid, predator, mycetophagous, frugivorous, palynivore, and nectarivorous group. Using Generalized Linear Mixed Models (GLMMs), we found that the abundance of phytophagous and predatory arthropods increases with leaf litter, while it decreases with saprophagous arthropods. Our findings suggest that tree-crop diversification within cocoa smallholdings can play a significant role in preserving higher arthropod biodiversity, particularly when these smallholdings remain free from chemical insecticide use. Canopy cover was also found to positively affect the variability of arthropods indicating that it is a crucial factor affecting arthropod biodiversity. This study underscores the significance of integrating agroforestry systems into cocoa production landscapes, particularly those utilizing agrochemicals, to support diverse arthropod communities and promote sustainable cocoa production.